Academic librarianship anchoring the profession in contribution, scholarship, and service - Simons, Marcy (Beta Phi Mu scholars series, 2021)
"This book is needed now as a response to how much has changed in academic librarianship as a profession (from the smallest academic libraries to large research libraries). Topics covered include: state of the profession of librarianship today, status of librarians, how are librarians conducting research, and more"--